Guiné Bissau, 30 anos de independência - Amado, Leopoldo (Africana Studia, 2020)
It is difficult, or even impossible, to try to understand the three decades that form Guinea-Bissau without proceeding to a deep auscultation of its colonial past and the history of its liberation war, such is the considerable weight the intensity that one and other aspect, although in a differentiated way, had and continue to have in the period post-independence. Thus, this article aims to establish a retrospective but equally prospective of the assessment of the three decades of the independence of Guinea-Bissau. It tries to reconstitute the essential lines and the lines of force that would come to strongly condition the process and the dynamics of the construction of the Guinean society. This analysis traverses the political, economic, social and cultural domains.